2020
DOI: 10.4314/ovj.v10i2.12
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of canine osteoarthritis with allogeneic platelet-rich plasma: review of five cases

Abstract: Background: Osteoarthritis (OA) is a major cause of chronic pain and lameness in dogs. Platelet-rich plasma (PRP) is a concentrate of growth and differentiation factors from the blood, which can be used in regenerative medicine strategies. Aim: The main aim of this study was to evaluate the effect of allogeneic PRP on the treatment of canine OA. Methods: Five dogs from several breeds, between 6 and 12 years old, and from both genders were studied. Clinical and imageological examinations diagnosed O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Among the orthobiologic blood products, particularly platelet products are already frequently used in clinical practice. In canine medicine, PRP or platelet concentrates have been used to treat several conditions, including osteoarthritis [ 17 , 18 , 19 , 20 ], lumbosacral stenosis [ 21 ], wounds [ 22 , 23 ], corneal ulcera [ 24 ], and aural hematoma [ 25 ]. While clinical benefits were shown, a major disadvantage of platelet concentrate is its limited long-term storage, as it cannot be frozen [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the orthobiologic blood products, particularly platelet products are already frequently used in clinical practice. In canine medicine, PRP or platelet concentrates have been used to treat several conditions, including osteoarthritis [ 17 , 18 , 19 , 20 ], lumbosacral stenosis [ 21 ], wounds [ 22 , 23 ], corneal ulcera [ 24 ], and aural hematoma [ 25 ]. While clinical benefits were shown, a major disadvantage of platelet concentrate is its limited long-term storage, as it cannot be frozen [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most of the PRP used for clinical treatment is prepared using autologous blood. However, some investigators have found that allogeneic P-PRP for the repair of bone defects can also achieve good efficacy [25][26][27]. In a randomized controlled clinical trial, allogeneic PRP was used in combination with standard care in chronic refractory wounds, and the results showed a significant reduction in inflammatory exudation and a significant reduction in healing time in wounds treated with allogeneic PRP [28].…”
Section: Discussionmentioning
confidence: 99%
“…The final product is then injected meticulously aseptically into the joint to avoid any infection. Duration of pain relief may last from 3 to 12 months and has been reported in OA dogs for PRP alone ( 195 – 199 ) or associated to HA ( 67 ) or physical therapy, showing longer duration of analgesia ( 197 ), APC ( 200 , 201 ), APS ( 187 , 202 , 203 ). Most interestingly, PRP may have the potential to slow the progression of the disease, as suggested by a recent metanalysis including 1,251 animals (19 studies on rodents, 13 on rabbits, 4 on horses, one on goats, and 7 on dogs) ( 204 ).…”
Section: Treatment Guidelinesmentioning
confidence: 99%